FRAMED BLACK IMAGE IN SCHOOL: under the discourse of equality - Rosangela Maria de Nazaré Barbosa e Silva; Wilma de Nazaré Baía Coelho (Editora da Universidade de Santa Cruz do Sul, 2010)
The study is part of the research project: "Black and High School: Representations of Teachers about Race Relations in the Curriculum," which analyzes the representations of teachers about race relations in the curriculum of the state high school. For this, mediate the results with some authors as: Silva (1997), Gomes (2002), Coelho (2006), CANEN (2001), Moreira (2006), Chartier (1991) and Bourdieu (1990), which have brought important contributions in training teachers about the racial issues in Brazil in (re) think the curriculum for diversity. Keywords: Representations of Professor - Curriculum - Race Relations - High School